2009
DOI: 10.1097/pai.0b013e318183a8e2
|View full text |Cite
|
Sign up to set email alerts
|

Podoplanin (D2-40) is a Highly Effective Marker of Follicular Dendritic Cells

Abstract: The monoclonal antibody D2-40 recognizes the membrane protein podoplanin, which is an established marker for germ cell tumors, mesotheliomas, and other tumor types and is also expressed in a variety of normal cells including follicular dendritic cells (FDCs). To determine whether podoplanin represents an effective FDC marker for pathologic lymph nodes, we compared immunohistochemical studies (sensitivity, staining patterns, and intensity of staining) for podoplanin (D2-40) with those of the traditional FDC mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…Of interest, several recent studies have shown that D2-40 is a highly effective marker for follicular dendritic cells and tumors of this origin. 25,35 Dendritic cells, including follicular dendritic cells, epidermal Langerhans cells, and dermal dendrocytes, are a heterogeneous group of antigen-presenting cells present in both lymphoid and non-lymphoid tissues. 36 Although each type differs in its ultrastructure, function, and morphology, dendritic cells from different sites share features of structure and function, such as the ability to capture antigens.…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, several recent studies have shown that D2-40 is a highly effective marker for follicular dendritic cells and tumors of this origin. 25,35 Dendritic cells, including follicular dendritic cells, epidermal Langerhans cells, and dermal dendrocytes, are a heterogeneous group of antigen-presenting cells present in both lymphoid and non-lymphoid tissues. 36 Although each type differs in its ultrastructure, function, and morphology, dendritic cells from different sites share features of structure and function, such as the ability to capture antigens.…”
Section: Resultsmentioning
confidence: 99%
“…There has been also reports for the podoplanin expression in osteocytes and osteoblasts [28], mesothelial cells [4,29], epidermal basal layer cells [4,10], choroid plexus epithelial cells, thymus type I epithelial cells, myoepithelial cells, prostate myofibroblasts, follicular dendritic cells, and immature cells like fetal germ cells and developing Sertoli cells [1,4,10,[29][30][31][32][33][34]. Elucidation of the common biological importance in these somatic tissues is required.…”
Section: Podoplanin Expression In the Oral And Other Tissuesmentioning
confidence: 99%
“…Tumor-induced platelet aggregation occurred early in the development of metastatic lesions, so it may be involved in cancer cell migration, invasion, metastasis, and malignant progression (4)(5)(6)(7)(8)(9)(10)(11)(12). Human podoplanin is expressed by several normal tissue cells, including: mesothelial cells (13,14), osteocytes and osteoblasts (1,13,15,16), stromal reticular cells, follicular dendritic cells of lymphoid tissue, ependymal cells of the central nervous system (CNS), and ovarian and testicular cells of both germ cell and sex-cord stromal origin, basal epithelial keratinocytes of the skin, cervix, and esophagus, and myoepithelial cells of the breast (1,5,6,14,(17)(18)(19)(20)(21)(22). Podoplanin is a useful marker of Kaposi's sarcoma (22)(23)(24), ONCOLOGY REPORTS 25: 599-607, 2011 599…”
Section: Introductionmentioning
confidence: 99%